Evaluation of polysaccharides from Laetiporus sulphureus on the growth of gastrointestinal probiotics and in vitro digestion - Zhu, Xinting; Lin, Shan; Wei, Qi (Frontiers in Sustainable Food Systems, 2024)
IntroductionProbiotics can improve immune responses and regulate the ecosystem of microorganisms in the gastrointestinal tract.MethodsThree primary models, including the Reparameterized Gompertz, Huang, and Baranyi and Roberts models were evaluated and developed to investigate the effects of Laetiporus sulphureus polysaccharides (LSP) on the growth of Lactobacillus plantarum, Streptococcus thermophilus, Clostridium tyrobutyricum, and Bifidobacterium adolescentis.ResultsThe Huang model and Reparameterized Gompertz model were suitable for describing the growth of C. tyrobutyricum, S. thermophilus, B. adolescentis, and L. plantarum. LSP could increase the population of B. adolescentis in the fluid environment of the stomach in vitro.DiscussionThese results may support the further development of LSP as a functional food or food additive that has the ability to preserve digestive tract health.